2020
DOI: 10.1002/rcr2.667
|View full text |Cite
|
Sign up to set email alerts
|

Hyper‐progressive disease after immune checkpoint inhibitor in SMARCA4‐deficient small‐cell lung carcinoma

Abstract: SMARCA4 (switch/sucrose non-fermentable-related, matrix-associated, actin-dependent regulator of chromatin, subfamily A, member 4)-deficient thoracic tumours have shown poor prognosis in clinical settings. Although the optimal treatment for SMARCA4-deficient thoracic tumours remains unclear, existing studies indicate a favourable response of these tumours to immune checkpoint inhibitors (ICIs). However, there are no reports of fatality in SMARCA4-deficient small-cell lung carcinoma (SCLC) with hyperprogressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Notably, there was one previous report that showed that PD-1 inhibitor was effective for a SMARCA4 deficient NSCLC patient with a high TMB and PD-L1 not highly expressed [9]. However, there was another study that reported hyperprogressive disease was obtained after immune checkpoint inhibitor treatment in SMARCA4 deficient SCLC [10].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there was one previous report that showed that PD-1 inhibitor was effective for a SMARCA4 deficient NSCLC patient with a high TMB and PD-L1 not highly expressed [9]. However, there was another study that reported hyperprogressive disease was obtained after immune checkpoint inhibitor treatment in SMARCA4 deficient SCLC [10].…”
Section: Discussionmentioning
confidence: 99%
“…A few therapeutic molecules targeting these genomic alterations are under development, most are being tested in vitro but some are also being evaluated in clinical trials. ICIs have been found to be efficacious in patients with SMARCA4 mutated or rearranged tumors 138,139 . However, cases of hyper progression after administration of ICIs have also been reported in these tumors 139 .…”
Section: Other Gene Fusions In Nsclcmentioning
confidence: 99%
“…ICIs have been found to be efficacious in patients with SMARCA4 mutated or rearranged tumors 138,139 . However, cases of hyper progression after administration of ICIs have also been reported in these tumors 139 . The morphological and phenotypical characteristics can sometimes point to the diagnosis, since these cancers can contain rhabdoid cells or even poorly differentiated cells associated with islets of epidermoid cells 135 .…”
Section: Other Gene Fusions In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…ICIs have been found to be efficacious in patients with SMARCA4-mutated tumors [267][268][269]. However, cases of hyper progression of tumors after administration of ICIs have been reported, too [270].…”
Section: Smarca4 Mutationsmentioning
confidence: 99%